Modelling of electromagnetic material properties at microwave frequencies - Alsadi, Majid Hamid Nassar (2012)
In recent years, electromagnetic interference (EMI) has raised serious issues in terms of the unintentional radiation that disrupts the near proximity equipment from working properly. One solution to reduce the effects of EMI is the use of electromagnetic shielding. Carbon fibre composite (CFC) material is a promising customised product that has entered numerous industrial areas due to its attractive properties like high strength, low weight, and the resistance to chemical substances and corrosion. CFC has started to be used as electromagnetic shields, for example modern computer cases. However, not much is known about its electromagnetic behaviour.